Cognitive processes in evaluating reference letters - Wong, Kin Fai Ellick; Werbel, James D. (Applied cognitive psychology, 2010)
This study simultaneously evaluates confirmatory information search theory and dual‐process theory in a selection process that uses reference letters as the evaluation tool. Confirmatory information search suggests that evaluators give attention to information that is congruent with first impressions. Dual‐processes theory suggests that evaluators give attention to information that is incongruent with first impressions. Using a sample of undergraduate students, in two separate experiments, we found that a poor impression from the résumé led to more positive information and less negative information searching in reference letters than did a good impression. These results of both experiments suggest that reference letter evaluators are likely to use cognitive processes associated with dual‐process theory. Copyright © 2008 John Wiley & Sons, Ltd.